Finite element modeling swift sheet metal formability test - Mohamad Faizul, Khoruddin (2009)
Sheet metal is one of the most important semi finished products used in the steel industry, and sheet metal forming technology is therefore an important engineering discipline within the area of mechanical engineering. Sheet metals are characterized by a high ratio of surface area to thickness. Sheet metal forming is basically conversion of a flat sheet metal into a product of desired shape without defect like fracture or excessive localized thinning. One of the techniques to determine the behavior or performance sheet metal is Swift Modeling Formability Test in ALGOR software. By this method, we can know the performance of the material such as ductility. For this project, there 3 types of materials had compare. Those materials are steel copper and aluminum. Developed of an appropriate die design for model in ALGOR software is important to getting the accurate results. Comparison between geometry types and material model also conducted in this project. The material was selected based on the frequent use in industry. The results we get from ALGOR software were transfer to Microsoft Excel to make the displacement graph. By that graph we can see the comparison of variable.